Chapter 7: Karl Polanyi - Rogerson, Kenneth S.; May, Christopher (Key Thinkers for the Information Society, 2002)
This article presents Karl Polanyi's analysis of the dynamic relationships between economy and society in the information age. Of the many concepts Karl Polanyi provides in his analysis of economic relations, three stand as carefully calculated assumptions about the relationship between society and economy: the embeddedness of information in society, the commoditization of information and the existence of a double movement in the information revolution. Information has always been embedded in societal interactions. To emphasize this point, he said that the simple flow of information seems to have little effect in and of itself on the outcome of social interchanges. In Polanyi's words, it is also embedded in other social relations, such as political, economic, cultural, or health-related discussions and actions. On the issue of information commoditization, Polanyi takes a different view. His logic indicates that there will be negative social consequences associated with it. One example is digital divide or the discrepancies on a global or national level between those who have access to information through new technologies and those who do not. With regards to the existence of double movement, Polanyi believed that there are two opposing forces-economic liberalism and social protection-present during the industrial revolution. However, this is not easy to see in the information age because of simple paradox. First, people who would eschew the uses of technology for ideological reasons,may turn to it for other reasons. And second, there is only a protest of a specific issue and not the imbalance of information flows or the ownership of information dissemination methods.
Keywords: commercialization; communication revolution; digital divide; industrial revolution; information technology; liberalism

The Great Depression and the Decline of Liberal Capitalism: Polanyi and Schumpeter - Trigilia, Carlo (Economic Sociology, 2002)
This chapter contains section titled: * Market Domination and Society's Self-Defense * The Decline of the Bourgeoisie and Anti-Capitalist Policies * Analytical Convergence and Political Divergence
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; capitalism; depression; economic level; economic sociology; international relations; social conditions